THE INFLUENCE OF PRICE, PERCEPTION OF PRODUCT QUALITY, AND SERVICE QUALITY ON CONSUMER BUYING INTEREST - Widya Avila Kristiati; Sengguruh Nilowardono (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the influence of perception of product quality and service quality on consumer buying interest. Product quality perception reflects consumers' assessment of product excellence and competitiveness, while service quality includes responsiveness, reliability, and empathy from service providers. Buying interest is an early indicator that reflects the likelihood of consumers to make a purchase. The research method used is quantitative with a survey approach, using questionnaires as a data collection tool. The research sample consisted of a number of respondents who had interacted with the products and services studied. The results of the analysis show that both the perception of product quality and service quality have a positive and significant influence on buying interest, both partially and simultaneously. These findings confirm the importance of improving product and service quality in marketing strategies to increase the purchasing potential of consumers.